Gas Exchange Rates Decrease and Leaf Temperature Increases in Nicotiana benthamiana Leaves Transiently Overexpressing Hemagglutinin in an Agrobacterium-Assisted Viral Vector System - Matsuda, Ryo; Ueno, Akihiro; Nakaigawa, Hirofumi; Fujiwara, Kazuhiro (Frontiers in Plant Science, 2018)
In this study, gas exchange characteristics and temperature of Nicotiana benthamiana leaves transiently overexpressing hemagglutinin (HA), an influenza vaccine antigen, with an Agrobacterium tumefaciens-assisted viral vector were investigated. Inoculation of leaves with an empty viral vector not containing the HA gene decreased the net photosynthetic rate (Pn) and transpiration rate (T) from 2 to 3 days post infiltration (DPI) in the A. tumefaciens suspension. Expression of HA with the vector decreased Pn and T to much lower levels until 4 DPI. Such significant decreases were not observed in leaves infiltrated with suspension of A. tumefaciens not carrying the viral vector or in uninfiltrated leaves. Thus, viral vector inoculation itself decreased Pn and T to a certain extent and the HA expression further decreased them. The decreases in Pn and T in empty vector-inoculated and HA expression vector-inoculated leaves were associated with decreases in stomatal conductance, suggesting that the reduction of gas exchange rates was caused at least in part by stomatal closure. More detailed gas exchange and chlorophyll fluorescence analyses revealed that in HA vector-inoculated leaves, the capacity of ribulose-1,5-bisphosphate carboxylase/oxygenase to assimilate CO2 and the capacity of photosynthetic electron transport in planta were downregulated, which contributed also to the decrease in Pn. Leaf temperature (LT) increased in viral vector-inoculated leaves, which was associated with the decrease in T. When HA vector-inoculated leaves were grown at air temperatures (ATs) of 21, 23, and 26°C post infiltration, HA accumulated earlier in leaves and the days required for HA content to attain its peak became shorter, as AT was higher. The highest LT was found 1–2 days earlier than the highest leaf HA content under all post-infiltration AT conditions. This phenomenon could be applicable in a nondestructive technique to detect the optimum harvesting date for individual plants to determine the day when leaf HA content reaches its maximum level, irrespective of spatiotemporal variation of AT, in a plant growth facility.